Deformation mechanisms and dynamic recrystallisation of Zr alloy with different initial textures compressed at 700°C. (July 2014) - Luan, B. F.; Li, X. Y.; Zhang, M.; Chapuis, Adrien; Liu, Q.
Abstract : The hot deformation behaviour depends on the initial texture. In this study a hot rolled Zr alloy plate with a bimodal basal texture has been compressed at 700°C along two directions to study the effect of initial texture on deformation mechanisms and dynamic recrystallisation (DRX). Four strain levels (10, 20, 30 and 45%) of uniaxial compression were analysed. Microstructures and textures of deformed specimens were characterized and compared by electron backscatter diffraction (EBSD). At 10% strain, twins were observed in the two textures, but 10–12 tensile twins predominate in the sample with the bimodal basal texture normal to the compression direction. As the compression strain accumulates to 20%, DRX is also affected by the initial texture. When the c-axis is close to the compression axis (CA), extensive DRX process was observed. If the c-axis is perpendicular to the CA, DRX was obviously retarded. Due to the initiation of twinning, the stored energy accumulated by dislocations was relatively low. After 45% compression, the two specimens developed the same bimodal basal texture with the c-axis of most grains rotated toward CA.